Mental Health Trainings in California's Higher Education System Are Associated with Increased Confidence and Likelihood to Intervene with and Refer Students - Osilla, Karen Chan (RAND Corporation, 2015)
Reports on an evaluation of California mental health trainings offered to staff and students in California's higher education system.